Examining Parental Perception of Inclusive Education Climate - Sharma, Umesh; Woodcock, Stuart; May, Fiona; Subban, Pearl (Frontiers in Education, 2022)
Parental perspectives about the inclusion of their child with a disability has received limited attention in the literature. Considering parental voice plays an important role in determining the quality of inclusive education, the lack of reliable and valid tools to investigate parental experiences has significantly limited research in this area. One of the key objectives of this study was to build the evidence base in the field by testing the psychometric properties of the newly developed Parental Perception of Inclusion Climate Scale, using a systematic approach drawing on a review of available research in the field. The scale incorporates items that address parental perspectives regarding six key aspects of inclusion for their child including presence, participation, acceptance, achievement, happiness and belonging. Participants were recruited through social media, and data from 190 parents of children with additional learning needs attending a range of school settings were collected. Results suggested a three-factor structure, with strong internal consistency for the scale. These factors were: Teacher and School Support; Student Engagement; and Friendships. The scale showed that parents are generally moderately satisfied with their child’s inclusion in school overall. A series of independent sample t-tests and one-way ANOVAs revealed significant differences in parental perspectives of inclusion as measured by the scale according to school sector, disability type, and parent gender. Parents whose children attend government schools reported less satisfaction with their child’s inclusion at school and also with the support provided by teachers and schools more broadly as measured by the Teacher and School Support subscale, as compared to parents of children who attend independent schools. Results also suggested that parents of children with a social emotional disability reported less satisfaction with their child’s engagement in school as measured by the Student Engagement subscale as compared to parents of children without a social emotional disability. Finally, fathers reported higher levels of satisfaction with their child’s engagement in school as measured by the Student Engagement subscale and also higher levels of satisfaction with their peer relationships as measured by the Friendships subscale than mothers. This study provides a tool that researchers, school educators, and policy makers could use to collect evidence about the efficacy of inclusive practices for students with a disability or additional support needs. The scale could provide educators and researchers with a valuable tool to guide evidence-based practice and theory in inclusive education.